Cutaneous Hypervascularization Treatment Using Photo-Mediated Ultrasound Therapy - Mingyang Wang; Rohit Singh; Wei Zhang; Jeffrey S. Orringer; Yannis M. Paulus; Xinmai Yang; Xueding Wang (Elsevier, 2023)
Photo-mediated ultrasound therapy (PUT) is a cavitation-based, highly selective antivascular technique. In this study, the effectiveness and safety of PUT on cutaneous vascular malformation was examined through in vivo experiments in a clinically relevant chicken wattle model, whose microanatomy is similar to that of port-wine stain and other hypervascular dermal diseases in humans. Assessed by optical coherence tomography angiography, the blood vessel density in the chicken wattle decreased by 73.23% after one session of PUT treatment in which 0.707 J/cm2 fluence laser pulses were applied concurrently with ultrasound bursts (n = 7, P < .01). The effectiveness of removing blood vessels in the skin at depth up to 1 mm was further assessed by H&E-stained histology at multiple time points, which included days 1, 3, 7, 14, and 21 after treatment. Additional immunohistochemical analyses with CD31, caspase-3, and Masson's trichrome stains were performed on day 3 after treatment. The results show that the PUT-induced therapeutic effect was confined and specific to blood vessels only, whereas unwanted collateral damage in other skin tissues such as collagen was avoided. The findings from this study demonstrate that PUT can efficiently and safely remove hypervascular dermal capillaries using laser fluence at a level that is orders of magnitude smaller than that used in conventional laser treatment of vascular lesions, thus offering a safer alternative technique for clinical management of cutaneous vascular malformations.